Total Antioxidant Capacity, Catalase and Superoxide Dismutase on Rats Before and After Diabetes - Celik, Sait; Akkaya, Hatice (Medwell Online, 2009)
This study is conducted in order to investigate the correlation between Superoxide Dismutase (SOD), Total Antioxidant Capacity (TAC) and Catalase (CAT). In this context, TAC, SOD, CAT, cholesterol, triglyceride, HDL and LDL were evaluated in 10 weeks old 20 healthy rats and 20 rats with experimentally-induced diabetes. Average SOD, CAT, TAC, HDL were found to be significantly lower in diabetes group than control group (p<0.05). But cholesterol, triglyceride and LDL were found to be significantly lower in control group than diabetes group (p<0.05). A correlation between SOD, CAT activity and TAC has been established both in control and diabetes group. In the result of the study, lower SOD, CAT and TAC levels were observed in diabetes group when compared to control group. According to the data obtained in this study, it was concluded that SOD, CAT and TAC are capable of serving as a parameter to monitor diabetes of patients with type 1 DM.
Keywords: Superoxide dismutase; catalase; antioxidants; diabetes mellitus; HDL; LDL